EFFECTS BY APPLYING A PLYOMETRIC TRAINING PROGRAM IN RUGBISTA BELONGING TO THE CATHOLIC UNIVERSITY OF TEMUCO (Fiep Bulletin - online, 2014)
In this study we present the results to the application of a plyometric program to rugby players of the Catholic University of Temuco, where after 16 training sessions to 8 players selected by one of the Bosco test seeks to find significant improvements in the ability of jumping to the players, where your physical abilities be heavily improved after training. This corresponds to evaluate three types of hops as the CMJ, SJ and Abalakov, with the aid of a jump platform through which accurate records indicate whether or not there is an improvement, and thus demonstrate and verify that the training influences plyometric jump improvements.
Keywords: Training; test Bosco; plyometrics; jump